2016
DOI: 10.14737/journal.jap/2016/3.2.56.60
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Ecto-Parasitic Infestation of Cattle in Milk Shed Areas of Baghabari of Shahjadpur Upazila of Sirajgonj District, Bangladesh

Abstract: | Epidemiological examination of 400 cattle for ecto-parasitic infestation in Baghabari milk shade area of Sirajgonj district, Bangladesh was recorded high amid the period from April 2014 to March 2015 revealed 60.00 per cent to be pervaded with several species of ticks and mites. The prevalence rate was highest in the case of Rhipicephalus sanguinus (20.00%) followed by Boophilus microplus (18.75%), Haematopinus eurysternus (11.25%) and Linognathus vituli (10.00%). The result disclosed that the infestation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…It was demonstrated that adult cattle were most susceptible to tick infestation (41.63%) followed by in calves (34.13%) and young cattle (29.94%). This finding has an agreement with other studies conducted in Sirajgonj (Hossain et al, 2016) and Gazipur of Bangladesh (Rony et al, 2010), Balochistan of Pakistan (Kakar et al, 2017), and Bahir Dar of Ethiopia (Gedilu et al, 2014). Disagreement with the findings of this study was observed with the findings of tick infestation in Chottogram district, Bangladesh (Kabir et al, 2011) and Mathura district, Uttar Pradesh, India (Patel et al, 2013]) where infection rate was much higher in calves.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was demonstrated that adult cattle were most susceptible to tick infestation (41.63%) followed by in calves (34.13%) and young cattle (29.94%). This finding has an agreement with other studies conducted in Sirajgonj (Hossain et al, 2016) and Gazipur of Bangladesh (Rony et al, 2010), Balochistan of Pakistan (Kakar et al, 2017), and Bahir Dar of Ethiopia (Gedilu et al, 2014). Disagreement with the findings of this study was observed with the findings of tick infestation in Chottogram district, Bangladesh (Kabir et al, 2011) and Mathura district, Uttar Pradesh, India (Patel et al, 2013]) where infection rate was much higher in calves.…”
Section: Discussionsupporting
confidence: 93%
“…In this research, tick infestation was highest in rainy season (43%) followed by summer (37.75%) and lowest in winter (27.50%). Similarities were found in tick infestation in Sirajgonj district where prevalence was highest in rainy season (74.55%) followed by summer (67.80%) and winter (42.44%) (Hossain et al, 2016). In India, highest prevalence of tick infestation occurred during rainy season (68.08%) followed by summer (59.85 %) and winter (48.70%) (Kaur et al, 2015).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition to D. bovis , three other species ( H. eurysternus , L. vituli , and S. capillatus ) were identified in Souk-Ahras. These latter are also among the species of lice encountered in Hungary [ 7 ], Tunisia [ 16 ], Canada [ 31 ], and Bangladesh [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rates of parasitism throughout Bangladesh are high due to its geographical position with a low‐laying area, heavy rainfall, and humidity (Hossain et al., 2016 ). Cattle are mostly susceptible to gastrointestinal parasites (GIPs), which have negative effects on the productivity and health of ruminants (Adua et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%